Ukraine - Improving Intergovernmental Fiscal Relations and Public Health and Education Expenditure Policy : Selected Issues - World Bank (Washington, DC, 2012)
This report concerns improving intergovernmental fiscal relations and public health and education expenditure policy in Ukraine. The large amount of resources the budget spends on services such as health and education, through its local government do not obtain good value. This is due to the acute inefficiency of service provision in these sectors, which generates under-spending on quality-enhancing expenditures and investments. The local governments are essential in providing and financing services such as health and education, and in channeling public investments across the country, and thus reforms in these sectors need to go hand-in-hand with intergovernmental fiscal reforms. Despite their large role in allocating spending, the ability of local governments to determine spending structure and to allocate expenditures within sectors is quite limited. The government needs to improve resource allocation by strengthening its intergovernmental fiscal system and by creating sufficient fiscal savings within the current fiscal envelopes of the health and education sectors in order to re-allocate these savings towards quality enhancing expenditures and investments within each sector.